The Gaussian Curvature Elastic Energy of Intermediates in Membrane Fusion - Siegel, David P. (The Biophysical Society, 2008)
The Gaussian curvature elastic energy contribution to the energy of membrane fusion intermediates has usually been neglected because the Gaussian curvature elastic modulus, κ, was unknown. It is now possible to measure κ for phospholipids that form bicontinuous inverted cubic (Q(II)) phases. Here, it is shown that one can estimate κ for lipids that do not form Q(II) phases by studying the phase behavior of lipid mixtures. The method is used to estimate κ for several lipid compositions in excess water. The values of κ are used to compute the curvature elastic energies of stalks and catenoidal fusion pores according to recent models. The Gaussian curvature elastic contribution is positive and similar in magnitude to the bending energy contribution: it increases the total curvature energy of all the fusion intermediates by 100 units of k(B)T or more. It is important to note that this contribution makes the predicted intermediate energies compatible with observed lipid phase behavior in excess water. An order-of-magnitude fusion rate equation is used to estimate whether the predicted stalk energies are consistent with the observed rates of stalk-mediated processes in pure lipid systems. The current theory predicts a stalk energy that is slightly too large, by ∼30 k(B)T, to rationalize the observed rates of stalk-mediated processes in phosphatidylethanolamine or N-monomethylated dioleoylphosphatidylethanolamine systems. Despite this discrepancy, the results show that models of fusion intermediate energy are accurate enough to make semiquantitative predictions about how proteins mediate biomembrane fusion. The same rate model shows that for proteins to drive biomembrane fusion at observed rates, they have to perform mediating functions corresponding to a reduction in the energy of a purely lipidic stalk by several tens of k(B)T. By binding particular peptide sequences to the monolayer surface, proteins could lower fusion intermediate energies by altering the elastic constants of the patches of lipid monolayer that form the stalk. Here, it is shown that if peptide binding changes κ or some other combinations of local elastic constants by only tens of percents, the stalk energy and the energy of catenoidal fusion pores would decrease by tens of k(B)T relative to the pure lipid value. This is comparable to the required mediating effect. The curvature energies of stalks and catenoidal fusion pores have almost the same dependence on monolayer elastic constants as the curvature energies of the rhombohedral and Q(II) phases; respectively. The effects of isolated fusion-relevant peptides on the energies of these intermediates can be determined by studying the effects of the peptides on the stability of rhombohedral and Q(II) phases.